Development of a fellowship training program in colorectal surgery - Asprer, Jonathan M. (2002)
Surgical diseases of the colon, rectum, and anus constitute a significant health problem in the Philippines. While many colorectal diseases can be adequately handled by general surgeons, a number of conditions require specialized knowledge, techniques, or technology that can only be acquired from a subspecialty training program. There is only one such training program in the country at present, and there are only twenty-six colorectal surgeons serving the entire Filipino population. Hence, the idea to establish such a program at the Jose R. Reyes Memorial Medical Center (JRRMMC) was first conceived in 1999 by the consultants of the Section of Colorectal Surgery, under the leadership of the Chairman of the Department of Surgery. The development of the program was intended to increase the capability to train more colorectal surgeons in the country and at the same time, enhance the training of General Surgery residents in colorectal surgery. This project describes the development of the second Colorectal Surgery Fellowship Training Program in the country. The methodology consisted of the following: 1) Initial discussions exploring feasibility of the project; 2) Review of the literature to support the rationale for establishing such a program; 3) Determination that the JRRMMC Colorectal Section would be able to fulfill the requirements promulgated by the Philippine Board of Colon and Rectal Surgery (PBCRS) for such a program; 4) Development of the research proposal; 5) Participation of content experts to determine perceived needs for the program in terms of trainee requirements and patient care; simultaneous with 6) Collation of published and web documents as references in developing the program curriculum and training program manual; 7) Ongoing consultation with content experts for feedback; and 8) Extensive revision and completion of documents. The products of this process are: 1) the Program curriculum, containing the program of study, intended learning objectives, course content, planned learning experiences and trainee evaluation for a one-year Fellowship Training Program in Colorectal Surgery; and 2) the Training Program Manual, the operations guide that outlines the implementation and management of the program, describing its structure and governance, and detailing the qualifications, duties and responsibilities of both trainers and trainees. It is recommended that this program be implemented at JRRMMC at the soonest possible time, and that other institutions with a similar intent in the future utilize this program as a guide.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Internship and Residency; Colon (Anatomy) -- Surgery